2004
DOI: 10.2133/dmpk.19.369
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Loxoprofen Interaction: Involvement of Human Organic Anion Transporters hOAT1 and hOAT3

Abstract: Human organic anion transporters hOAT1 (SLC22A6) and hOAT3 (SLC22A8) are responsible for renal tubular secretion of an antifolic acid methotrexate, and are considered to be involved in drug interaction of methotrexate with nonsteroidal anti-inflammatory drugs (NSAIDs). In our hospital, a delay of methotrexate elimination was experienced in a patient with Hodgkin's disease, who took loxoprofen, a commonly used NSAID in Japan, which suggested a cause. In this study, we examined the drug interaction via hOAT1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 20 publications
7
48
0
4
Order By: Relevance
“…Our current results were also consistent with the findings of Lu et al (1999), who cloned hPAHT (p-aminohippurate transporter, the first name of hOAT1), which exhibited no significant MTX uptake activity. Uwai et al (2004) determined the K m value for hOAT1-mediated MTX uptake using a Xenopus laevis oocytes expression system to be 724 mM. In fact, this higher value of K m for hOAT1 supported our result, i.e., this concentration was not clinically relevant (Uwai et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our current results were also consistent with the findings of Lu et al (1999), who cloned hPAHT (p-aminohippurate transporter, the first name of hOAT1), which exhibited no significant MTX uptake activity. Uwai et al (2004) determined the K m value for hOAT1-mediated MTX uptake using a Xenopus laevis oocytes expression system to be 724 mM. In fact, this higher value of K m for hOAT1 supported our result, i.e., this concentration was not clinically relevant (Uwai et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…Several drugs, including nonsteroidal anti-inflammatory drugs (Nozaki et al, 2007;Uwai et al, 2004;Maeda et al, 2008), penicillin G (Takeda et al, 2002b), and probenecid (Aherne et al, 1978), are known to inhibit the elimination of MTX. The molecular mechanism underlying these interactions partially relies on the blockade of the renal secretion of antifolate via the basal uptake transporters hOAT3 and hOAT1 (Giacomini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A previous retrospective study demonstrated that the coadministration of NSAIDs was not a risk factor for the development of hematologic toxicity by pemetrexed (Sakata et al, 2013); however, NSAIDs are known as substrates and/or inhibitors of hOAT3 (Uwai et al, 2004;Nozaki et al, 2007). A clinical study has reported that a 20% increase in the area under the plasma concentration curve of pemetrexed was observed when 400 mg of ibuprofen was administered orally every 6 hours .…”
Section: Discussionmentioning
confidence: 99%
“…18,19) In addition, Deguchi et al reported no effect of 1 mM indomethacin on rOAT3, but the drug at 0.1 mM inhibited hOAT3 moderately. 20,21) Kynurenic acid and xanthurenic acid are closely related compounds. It is unique that rOAT3 showed similar transport activities for the two compounds, but that hOAT3 exhibited different.…”
Section: Discussionmentioning
confidence: 99%